Benefits of plant cell suspension on vesicular-arbuscular mycorrhizal fungi in vitro. II. Effects of cell concentration and cell viabillity - Paula, Mauro Augusto de; Siqueira, José Oswaldo; Pinto, José Eduardo Brasil P.; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 2014)
The effects of addition of 0, 500, 1,000, 1,500, 3,000 and 6,000 of pueraria cell suspension per 20 ml of medium and cell viability on spore germination and germ tube growth of vesicular arbuscular mycorrhizal fungi were studied in agar and liquid media. Additions of 500 viable pueraria cells gave the greatest benefits to either germination or mycelial growth. On the other hand, addition of dead cells had no significant effects on the spores. This result indicates that the beneficial effects of plant cell suspension depend upon their metabolic activity. It was also found that the presence of viable plant cells did not stimulate independent growth of hyphae after detachment of the parent spore.